Splanchnic and Systemic Hemodynamics in Cirrhotic Patients With Refractory Ascites. Effect of Peritoneovenous Shunting. Issue 4 (1991) - Vons, Corinne; Hadengue, Antoine; Lee, Samuel S.; Smadja, Claude; Franco, Dominique; Lebrec, Didier
Abstract : The splanchnic and systemic hemodynamics of 14 patients with refractory ascites were studied and were compared to those of 15 patients with ascites responding to medical treatment. Among the 14 patients, 10 were grade B and 4 C, according to the Pugh classification. Of the 15 patients, 5 were Pugh B and 10 C. In patients with refractory ascites, free hepatic venous pressure was significantly higher and hepatic venous pressure gradient was significantly lower than in patients with responsive ascites. Hepatic and azygos blood flows were not significantly different between the two groups. Cardiac output was lower in patients with refractory ascites (p < 0.05) than in those with responsive ascites. In patients with refractory ascites, six months after peritoneovenous shunting, there was a significant reduction of wedged and free hepatic venous pressures and azygos blood flow. Cardiac output increased by 20% (p < 0.02). This study shows that hemodynamic alterations in patients with refractory ascites is the consequence of increased intraabdominal pressure due to chronic ascites. Six months after peritoneovenous shunting splanchnic and systemic hemodynamics became similar to those observed in patients without ascites.